2021
DOI: 10.14366/usg.20028
|View full text |Cite
|
Sign up to set email alerts
|

Renal growth slope in children with congenital and acquired solitary functioning kidneys

Abstract: Purpose: This study aimed to analyze the renal growth slope in children with congenital and acquired solitary functioning kidneys. Methods: This retrospective study included all renal ultrasonography examinations performed in children in the agenesis, multicystic dysplastic kidney (MCDK), or nephrectomy group between September 2002 and February 2019. We reviewed the images and recorded the contralateral kidney size only when there was no focal lesion. Linear mixed model or piecewise linear mixed model analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The minimum eGFR was determined as 71 mL/min/1.73 m 2 . In previous studies, the rate of reduced eGFR in patients with SK was reported as 8.4%, 4 1.3%, 10 and 10.6% 20 . Abou Jaoude et al detected higher eGFR in patients with CSK compared to the ASK group and noted the presence of a negative correlation between eGFR and both age and follow‐up time 17 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The minimum eGFR was determined as 71 mL/min/1.73 m 2 . In previous studies, the rate of reduced eGFR in patients with SK was reported as 8.4%, 4 1.3%, 10 and 10.6% 20 . Abou Jaoude et al detected higher eGFR in patients with CSK compared to the ASK group and noted the presence of a negative correlation between eGFR and both age and follow‐up time 17 .…”
Section: Discussionmentioning
confidence: 95%
“…In previous studies, the rate of reduced eGFR in patients with SK was reported as 8.4%, 4 1.3%, 10 and 10.6%. 20 Abou Jaoude et al detected higher eGFR in patients with CSK compared to the ASK group and noted the presence of a negative correlation between eGFR and both age and follow-up time. 17 We also observed that the children with CSK had significantly higher eGFR than those with ASK (p < 0.001); however, we did not detect a correlation between eGFR and age or follow-up time.…”
Section: Discussionmentioning
confidence: 98%